Phonological Disorders of Children with Down Syndrome Based on the Level of Intelligence: A Case Study - Joko Prowoto; Gusdi Sastra; Amel Yanis (IAIN MADURA, 2019)
Many of speech therapists have given therapy to the children with Down Syndrome (DS) without thinking whether the children belong to mild mental retardation (IQ 50-69) or moderate mental retardation DS children (IQ 35-49). Therefore, a study was conducted to see the differences and the findings showed that the moderate mental retardation DS child dominated the three types of phonological disorders, i.e. phoneme substitution, simplification, and addition. In this research, the last type of phonological disorder was not found for both DS children. In addition, the mild mental retardation DS child responded the stimulus, yet the moderate mental retardation DS child could not answer about 1/5 stimulus given. It was also found that the moderate mental retardation DS child was so sensitive with touching. So, the therapy for the DS should not be the same. For the mild mental retardation DS children (IQ 5-069), the stimulus given to them could be by using flash cards, but for the moderate mental retardation down syndrome children (IQ 35-49), the stimulus should be something real, concrete, or something that could be touched so that they can respond the stimulus well and their language can be better in the future.